Bilaminar Structure of the Human Optic Nerve Sheath. (2nd July 2020) - Le, Alan; Shin, Andrew; Park, Joseph; Poukens, Vadims; Demer, Joseph L.
ABSTRACT: Purpose/Aim: We aimed to characterize the connective tissue microanatomy, elastin abundance, and fiber orientation in the human optic nerve sheath, also known as the optic nerve dura mater, for correlation with its biomechanical properties. Materials and Methods: Seven whole human orbits aged 4–93 years, and five isolated human optic nerve sheaths aged 26–75 years were formalin fixed, paraffin embedded, coronally sectioned, stained by Masson trichrome and van Gieson's elastin methods, and analyzed quantitatively for elastin fiber abundance and orientation. Elastin area fraction was defined as area stained for elastin divided by total area. Results: While unilaminar in children, the adult ON sheath exhibited distinct inner and outer layers. Collagen was denser and more compact in the inner layer. Elastin area fraction was significantly greater at 6.0 ± 0.4% (standard error of mean) in the inner than outer layer at 3.6 ± 0.4% ( P < 10 −5 ). Elastin fibers had three predominant orientations: longitudinal, diagonal, and circumferential. Of circumferential fibers, 63 ± 4.7% were in the inner and 37 ± 4.7% in the outer layer ( P < 10 −4 ). Longitudinal and diagonal fibers were uniformly distributed in both layers. Elastin density and sheath thickness increased significantly with age ( P < .01). Conclusions: The adult human optic nerve sheath is bilaminar, with each layer containing elastin fibers oriented in multiple directions consistent with isotropic properties. Differences in laminar elastin density and orientation may reflect greater tensile loading in the inner than in the outer layer.